TOWARD A DYNAMIC VIEW OF SECOND LANGUAGE COMPREHENSIBILITY - Nagle, Charles; Trofimovich, Pavel; Bergeron, Annie (Studies in second language acquisition, 2019)
This study took a dynamic approach to second language (L2) comprehensibility, examining how listeners construct comprehensibility profiles for L2 Spanish speakers during the listening task and what features enhance or diminish comprehensibility. Listeners were 24 native Spanish speakers who evaluated 2–5 minute audio clips recorded by three university-level L2 Spanish speakers responding to two prompts. Listeners rated comprehensibility dynamically, using Idiodynamic Software to upgrade or downgrade comprehensibility over the course of the listening task. Dynamic ratings for one audio clip were video-captured for stimulated recall, and listeners were interviewed to understand which aspects of L2 speech were associated with enhanced versus diminished comprehensibility. Results indicated that clips that were downgraded more often received lower global ratings but upgrading was not associated with higher ratings. Certain problematic features and individual episodes caused listeners’ impressions to converge, though substantial individual variation among listeners was evident.